Future diagnosis, today's treatment – cardiomyopathy in the course of psoriasis: a case report. Issue 6 (25th March 2013) - Pietrzak, Aldona; Brzozowska, Anna; Lotti, Torello; Mosiewicz, Jerzy; Wysokiński, Andrzej; Mieczkowska, Jolanta; Hercogova, Jana; Bartosińska, Joanna; Juszkiewicz‐Borowiec, Maria; Chodorowska, Grażyna
Abstract Psoriasis is a relatively common, chronic skin disease of inflammatory origin. In recent years, public attention has been drawn to a more and more frequently observed relationship between psoriasis and cardiovascular disease. Nowadays, psoriasis is independently held responsible for increased cardiovascular mortality. It seems that the actual significance of the problem, together with a heart‐related death risk for these patients is often underestimated. This study presents clinical evidence collected during a long‐term observation and treatment of an 80‐year‐old psoriatic patient with concomitant diabetes, hypertension, and ischemic heart disease, whose overall clinical picture also suggested a congestive, inflammation‐related cardiomyopathy with conduction disorders and severe heart failure. Despite the patient's advanced age and associated serious, long‐established psoriasis‐related problems, he was successfully treated with the use of interventional cardiology methods, as well as cardiac resynchronization therapy.